Analisis Tarik-Menarik Otoritas Pengawasan Baitul Maal Wat-Tamwil (BMT) antara Kementerian Koperasi dan Otoritas Jasa Keuangan - Nindya Octariza; Muh Rizwan Azzahidi (ISLAMIKA, 2023)
BMT (Baitul Maal-wat-Tamwil) is one type of financial institution regulated by the OJK or the Financial Services Authority, whose job is to regulate licensing, training and supervision. This rule was made based on Article 6 of the Financial Services Jurisdiction Law No. 21 of 2011, which authorize OJK to regulate, monitor, and administer licensing procedures for all financial services sector. As a legal issues have been regulated, although they do not play a significant role in their oversight. OJK acts as supervisory agency for the country’s financial service industry, creating an integrated regulatory and supervisory structure for all operations in the financial services sector. Law no. 1 of 2013 authorized. Article 5 paragraph 2 POJK No. 12/POJK.05/2014 confirms this. The author’s research approach is literature study. The legality of BMTs has not chaged, and many BMTs still prefer the legal cooperative form. This has consequences in the form that BMT is governed by rules governing cooperatives, particularly Law No. 25 of 1992.